Análise da cinética do VO2 no domínio severo do crawl em condição atada de nado - Siqueira, Leandro Oliveira da Cruz [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Major concernments about the available data on swimmer's aerobic capacity assessed during tethered-swimming are (1) devise technology to sample oxygen uptake (VO2), (2) temporal mismatching of gas exchange response to underlying physiological process, and (3) undiscernible markers for threshold discrimination from ventilatory parameters. Therefore, the aimed was designs an incremental tether-test (ITT) with step workload (WL) based on individual rates of maximal tether-force (Fmax) in crawl stroke, and thus identifies the lactate threshold (LT), by means of gas exchange response (GET), and respiratory compensation point (RCP). Eleven males (18.0 ± 4.0 years old, 180.2 ± 6.8 cm height, and 71.8 ± 9.5 kg body weight) and five females (16.8 ± 3.6 years old, 166.2 ± 5.5 cm height, and 61.1 ± 9.8 kg body weight) swimmers performed an ITT until volitional exhaustion attached to a weight-baring pulley-rope system to the assessment of GET, RCP and maximal aerobic power (VO2max). WL was incremented from 30 to 70% of Fmax, with step rate of 5% every minute. Fmax was measured with a 500kgf load cell attached to the swimmers by an inelastic rope, during full-crawl all-out bout lasting 30-s. Pulmonary gas exchange was sampled breath-by-breath (CPET K4b2) connected to a specific snorkel (new AquaTrainer). GET criteria were: rising in VE/VO2 with no concomitantly changes on VE/VCO2; and PCR criteria were: sustained increasing in both VE/VO2 and VE/VCO2. Mean VO2max approached 52.4 ± 4.9 mlO2×kg-1×min-1 and 45.4 ± 6.0 mlO2×kg-1×min-1 ...

Principais interesses sobre os dados disponíveis sobre a capacidade aeróbia de nadadores avaliados durante o nado atado são (1) conceber tecnologia para analisar o consumo de oxigênio (VO2), (2) dissociação temporal da resposta da permuta gasosa para o processo fisiológico subjacente, e (3) marcadores indiscerníveis para discriminação dos limiares dos parâmetros ventilatórios. Portanto, o objetivo foi projetar um teste incremental atado (ITT), com carga de trabalho progressiva (WL) com base nas taxas individuais de força máxima atada (Fmax), em estilo crawl e, portanto, identificar o limiar de lactato (LT), Limiar de Permuta Gasosa (GET) e Ponto de Compensação Respiratória (PCR). Onze homens (18,0 ± 4,0 anos, 180,2 ± 6,8 cm e 71,8 ± 9,5 kg), nadadores realizaram um teste incremental atado máximo (ITT) até a exaustão voluntária para avaliar o VO2max. nadadores realizaram o ITT, atados a uma polia de carga pelo tronco, até a exaustão voluntária para encontrar o limiar de permuta gasosa (LPG), o ponto de compensação respiratória (PCR) e a potência aeróbia máxima (VO2max). Houve o aumento da carga de trabalho incremental, de 30 a 70 % da Fmax com incremento de 5% por minuto. O valor de Fmax foi obtido por célula de carga de 500kgf em um teste máximo com duração de 30 s. A permuta gasosa foi coletada, respiração a respiração por um analisador de gases portátil (COSMED K4b2) conectado ao nadador por um snorkel específico (new-AquaTrainer) LPG e PCR foram examinado visualmente, usando as respostas dos parâmetros VE/VCO2, VE/VO2, PETCO2 e PETO2. Os critérios para determinar o LPG foram: aumento na curva da...
VO2 kinetics analysis during swimming at severe domain in tethered-crawl condition
Keywords: Swimming; Natação; Nado atado; Nado crawl; Capacidade aeróbia; Oxigenio - Consumo